Pengaruh Latihan Interval Intensitas Sedang (MIT) Terhadap Peningkatan Vo2 Max Pada Atlet Renang Putra Althario Swimming Class Di Kota Bengkulu - Yogen Ahmad Yuzendi; Citra Dewi; Martiani Martiani (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to determine the Effect of Moderate Intensity Interval Training (MIT) on Increasing Vo2 Max in Male Swimmers at Althario Swimming Class in Bengkulu City. This study is a study that uses a pre-experiment with a One Group Pretest-Posttest Design. The sample in this study were 10 male swimmers at Althario Swimming Class. The data collection technique was by conducting a Vo2max test. Then an analysis was carried out according to the existing test results. The results of the study showed that the average value of VO₂ Max before moderate intensity interval training was given was 42.35 ml/kg/minute, whereas after the training was given, the value increased to 47.11 ml/kg/minute. The average difference in increase reached 4.76 ml/kg/minute, which is equivalent to an increase of about 11.2% relatively.